Towards Paraconsistent Engineering - Akama, Seiki; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents a collection of contributions from related logics to applied paraconsistency. Moreover, all of them are dedicated to Jair Minoro Abe,on the occasion of his sixtieth birthday. He is one of the experts in Paraconsistent Engineering, who developed the so-called annotated logics. The book includes important contributions on foundations and applications of paraconsistent logics in connection with engineering, mathematical logic, philosophical logic, computer science, physics, economics, and biology. It will be of interest to students and researchers, who are working on engineering and logic. .
Introduction -- Why Paraconsistent Logics? -- An Application of Paraconsistent Logic to Physics: Complementarity -- Two Genuine 3-Valued Paraconsistent Logics -- A Survey of Annotated Logics -- A Paraconsistent Artificial Neural Network for Structuring Statistical Process Control in Electrical Engineering -- Programming with Annotated Logics -- A Review on Rough Sets and Possible World Semantics for Modal Logics -- Paraconsistency, Chellas's Conditional Logics, and Association Rules -- A Beautiful Theorem.-Temporal Logic Modeling of Biological Systems -- Jair Minoro Abe on Paraconsistent Engineering.
Keywords: Computational intelligence; Artificial intelligence; Mathematical logic; Logic; Computer science; Computational Intelligence; Artificial Intelligence; Mathematical Logic and Foundations; Logic; Computer Science Logic and Foundations of Programming